Development Policy Process in Nepal: A Critical Analysis (The International Research Journal of Management Science, 2019)
The article analyzes the development policy, agenda sources, policy formation, implementation, and evaluation process of Nepal. The description of policy agendas, role of the National Planning Commission (NPC) as development policy agency, trend of planned development approach in Nepal its review target achievements and discussion of identified problems of development plans are also the contents of the article. It further explains the explored problems and ideas to solve them in a complete development policy process Nepal. The article examines the level of social justice analyzing whole development policy process of Nepal along with the interpretation of policy agency through the lance of power sharing based on thematic analysis of data. The article has concluded that the current development policy process is centralized, top-down and elite dominated in a old tendency which is not compatible process to federal structure of Nepal. The reformation of this old tendency through inclusive, bottom-up approach and deconstruction of centralization with insurance of multi-dimensional meaningful participation and ownership development to the concerned stakeholders in all levels is the way of solution. The reformation is necessary in both policy agency institutional structure and policy process of development, such as:, agenda setting, situation analysis, alternative selection, policy adoption, and implementation with due monitoring and evaluation process for the bright future of Nepali peoples.